A fast pothole repair method using asphalt tiles and induction heating. (30th January 2017) - Obaidi, H.; Gomez-Meijide, B.; Garcia, A.
Graphical abstract: Highlights: Asphalt tiles are used to fill potholes and bonded using induction heating. The shear strength of the bond is higher than the original materials. The rutting resistance is 40 times higher than cold mix asphalt. Abstract: In this paper, a new method to repair potholes in asphalt roads is presented. It consists of an asphalt mixture tile with a bottom bonding layer made of bitumen, and steel fibres. To use this technology, potholes have to be first cleaned, second filled with an asphalt tile and third, exposed to high frequency electromagnetic fields to heat the fibres up and melt the bitumen in the bonding layer. This article assess the bonding properties of tiles built with bonding layers of various thicknesses and amounts and distributions of fibres. Furthermore, the effect of moisture on the bonding properties of asphalt tiles has been examined and the functionality of the tiles observed using wheel track tests. It has been concluded that asphalt tiles are a suitable method to repair potholes, and the durability of the repaired surface is comparable to that of a newly built road.